A systematic investigation on the minimum tensile strengths and size effects of 3D printing polymers. (January 2023) - Zhang, Gonghe; Wang, Qinglin; Ni, Yinxu; Liu, Pei; Liu, Fenghua; Leguillon, Dominique; Xu, Luoyu Roy
Abstract: Unlike isotropic homogenous materials, 3D printing polymers are anisotropic in terms of their strength and fracture toughness properties, according to previous research. Therefore, the lowest strength must be accurately measured before the extensive application of any 3D printing materials. Certain 3D printing materials have been increasingly employed in large structures; therefore, the size effect of their strengths has become very important. In this work, we performed a systematic experimental investigation on the minimum strengths and size effects of four common 3D printing polymers made by fusion deposition modeling and injection molding. Three types of tensile specimens with very different cross-sectional areas were selected. For each material system, two types of specimens with different printing surface angles were employed. The results from 200 specimens demonstrated that the minimum tensile strengths in the build direction of some specimens were only 25% that of the other directions in the same specimens, and 59% of the injection-molded specimens composed of the same material. No general conclusion on the size effects of the tensile strengths could be made for most specimens. Only the strengths along the build direction decreased up to 72% in two types of specific specimens if their cross-sectional areas increased by 60 times. Although their strengths were anisotropic, the stiffness properties of the 3D printing polymers were isotropic. Digital image correlation measurements showed that the Young's moduli of all specimens composed of the same material were similar. A dual-notch mechanics model was employed to explain the anisotropic strengths, and a fractography analysis supported the size effect. Graphical abstract: Image 1 Highlights: Tensile strength along the build direction was the minimum strength. No general conclusion on the size effects of the tensile strengths could be made. Strengths decreased 72% in only PLA and PC specimens if their areas increased by 60 times.